The characteristic of factorial structure of the general(common) physical readiness of girls of 11-15 years - Козіна, Ж. Л.; Попова, Н. (Physical Education Theory and Methodology, 2013)
In work are submitted results of pedagogical testing of girls of 11-15 years under the state tests of Ukraine. The factorial analysis of parameters of testing for each age group was carried out(spent). It was revealed, that structure of physical readiness of girls of 11-15 years different for each age group. It is necessary for taking into account at construction of lessons of physical culture and training employment(occupations) on any kinds of sports. Key words: physical readiness, factorial structure.